Ոսկանյան Աստվածաշնչի եւ ԺԷ. դարի հայերեն ձեռագիր Աստվածաշնչերի պատկերագրական աղերսները - Արփինե Սիմոնյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В 1662 г. Воскан Ереванци по поручению Акопа Джугаеци отправляется в Европу для издания Библии на армянском языке. Осенью 1664 г. он берется за руководство типографией св. Эчмиадзина и св. Саргиса в Амстердаме и вместе с учениками Карапетом Адрианаци и Оганом Ереванци начинает печатать Библию, издание которой заканчивается в 1668 г. Все издания Воскана Ереванци отличаются высоким качеством и изысканным оформлением. In 1662, on recommendation of Hakob of Julfa, Voskan of Yerevan went to Europe in order to publish the Bible in Armenian. In 1664 Voskan of Yerevan took charge of the publishing house of Holy Etchmiadzin and St. Sarkis, and together with his students Karapet of Adrian and Ohan of Yerevan began and in 1668 fi nished the publication of the Bible. The publications of Voskan of Yerevan are distinguished with their gorgeous illustrations.
Keywords: Bibliography; The Bible; Printing